Clinical outcomes of pharmacological therapies for heart failure in Black vs. White populations: a meta-analysis of randomized controlled trials of heart failure treatment - Li, Yujia; Tang, Huilin; Huang, Wenxi; Chen, Wei-Han; Chang, Shao-Hsuan; Bian, Jiang; Ahmed, Mustafa M.; Kimmel, Stephen E.; Guo, Jingchuan (Frontiers in Cardiovascular Medicine, 2025)
ObjectiveTo evaluate the effect of different pharmacological therapies for heart failure (HF) between the Black vs. White population.MethodWe included randomized controlled trials (RCT) of HF pharmacological therapies with explicit strata of Black or White adults in the primary or secondary analysis. We examined three outcomes: (1) the composite of CV death or hospitalization for heart failure (HHF), (2) HHF, and (3) all-cause death. Within each race (White and Black), we calculated the pooled risk ratio (RR) with a 95% confidence interval (CI) of different pharmacological therapies using random-effects models. Within each pharmacological therapies, we assess the differences in the treatment effect by race.ResultsIn 19 RCT reporting eight pharmacological therapies, there was no significant difference between the Black and White groups for using sacubitril/valsartan, angiotensin-converting enzyme inhibitors, calcium-channel blockers, direct renin inhibitors, oral soluble guanylate cyclase, or vasodilators. Sodium-glucose cotransporter-2 inhibitors (SGLT2i) had a different effect in HHF across the White and Black patients (Pinteraction = .030), with a better treatment effect observed in the Black (RR 0.39, 95% CI 0.19–0.80) compared to the White group (0.90, 0.71–1.14). Beta-blockers had a better treatment effect in the White (0.65, 0.52–0.81) compared to the Black group (1.14, 0.88–1.47) regarding the all-cause death outcome (Pinteraction = .001).ConclusionBlack individuals with HF appeared to obtain a greater benefit of HHF risk reduction from SGLT2i and less benefit for mortality from beta-blockers compared to their White counterparts.